The impact of China's high-tech repression on Uyghurs: a case study of Uyghur diaspora in Turkiye - Oztig, Lacin Idil; Karluk, Abdurresit Celil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
There is a plethora of research on the determinants of state repression. Concomitant with the advancement of technology, there is a growing body of literature on high-tech repression. However, relatively scarce attention has been paid to the impact of high-tech repression on individuals. This study makes a novel contribution to the literature by analysing the impact of China's high-tech repression in East Turkestan on the identity, beliefs and practices of Uyghurs. We analyse the impact of state surveillance in East Turkestan based on surveys and focus group interviews with members of the Uyghur diaspora (who experienced China's repressive practices in the region and subsequently migrated to Turkiye) between July and September 2023. The overwhelming majority of the survey respondents indicated that high-tech repression severely reduced their social interactions and cultural practices in East Turkestan and that this repression has negatively affected their view of the Chinese state and technology in general. Most of the respondents indicated that after witnessing this type of repression, they clung more to their national identity. Our focus group interviews provide more in-depth results on the impact of high-tech repression. The participants shared their experiences of how constant surveillance disrupted their daily lives, neighbourly relations, mobility and personal well-being.
Keywords: China; East Turkestan; Uyghurs; high-tech repression; surveys; focus group interviews; STATE REPRESSION; SURVEILLANCE; POWER; Area Studies